A comparison framework between types of electric system operators. The uniqueness of the Brazilian case in the context of hydro-dominated systems - Marcu, Oana Simona (2009)
First and foremost, this research project develops a framework for analyzing electric system operators ( ESOs ). A deep literature survey is invoked to inventory the responsibilities of these institutions; then, a graphical model is developed so as any type of operator can be represented. This framework is useful to create comparisons between operators and understand the different nature of the responsibilities they are charged with, in connection with the particularities of their electric sectors. This framework was developed with the precise aim to benchmark the Brazilian operator against similar entities, yet it can be used for any country with an at least functionally unbundled ESO. Canada, Norway and Colombia were chosen due to the high percentage of hyroelectricity in their electricity generation capacity and production matrixes, a characteristic that is similar to the Brazilian case. Nevertheless, the study finds that the Brazilian operator s particularities owe mainly to the uniqueness of the electricity context, despite a few transaction costs between institutions than can possibly be reduced.